Pemanfaatan Aplikasi Multifungsi Sebagai Perantara dalam Penanganan Limbah dalam Rangka Responsible Consumption and Production - Erilia Kesumahati; Joycelin Joycelin; Angelina Julia Renaldi; Catherine Catherine; Jesslyn Jesslyn; Alex Alex (LPPM Universitas Internasional Batam, 2023)
Consumption and production activities are inseparable from human daily life, so it cannot be denied that these activities produce unwanted impacts which have the potential to harm the surrounding environment such as waste. Therefore, efforts and potential handling are needed to realize the handling of responsible consumption and production. This activity aims to analyze current social problems and overcome them by planning community service programs through entrepreneurship. The research method used in analyzing this article is a quantitative and qualitative method, which includes direct observation or through social media of the problems being faced by the community and analyzing the results of survey questionnaires on programs that have been designed in the form of Google form. The process of implementing activities starts from evaluating the surrounding environment and the results of the evaluation will be used to plan activities to overcome these problems. After that, prepare activities by looking for partners and making prototype applications that will start carrying out activities. Finally, collect ratings and feedback from users regarding our designed applications. The end result of this application design is to become an intermediary application in realizing responsible consumption and production handling through the features provided such as educational features, channeling features, and other features that support waste reprocessing activities. With this application, it is hoped that it can create a cleaner environment and free from waste pollution with efforts to minimize and reuse waste through the application features provided.